Identifikasi Telur Hymenolepis Nana Dan Hymenolepis Diminuta Pada Feses Tikus Dan Feses Anak-Anak Di Dukuh Sraten, Kecamatan Pedan, Klaten - Ika Ayu Habsari; Tri Mulyowati (Journal of Health (JoH), 2020)
Rats are animals that are susceptible to being infected with dengerous diseases because they like dirty environments. Hemintheasis spread by rats, namely hymenolepiasis.transsmision of this worm disease can occur directly and indirectly. Direct trasmission is caused by consuming water or food contaminated with worm egg while direct trasmission occur through intermediate fleas. The purpose of the study was to determine the presence of Hymenolepis Nana dan Hymenolepis Diminuta eggs in rats faeces and childern’s faeces in hamlet sraten, and to find out what percentage of faeces of mice and faeces of childern’s infected with Hymenolepis Nana dan Hymenolepis Diminuta. The method used is direct method which is macroskopis and microskopis and indirect method of sedimentation examination. Faecel sampling is done by simple random sampling. Based on the results of examination of 30 rats samples and 17 faeces samples the childern obtained result of second faeces samples of mice positively infected with Hymenolepisdiminuta eggs or at 6,67%, in the childern’s faeces samples not Hymenolepis Diminuta eggs were found. Whereas Hymenolepis Nana infection was not found in the rat faeces samples or childern’s faeces samples or with a negative 100% percentage.